The Greek Economy in the Post-Maastricht Era: Challenges and Policy Perspectives - Katseli, Louka T. (Études helléniques / Hellenic Studies, 1997)
The author of this article analyses the new challenges facing the Greek economy in view of the Treaty of Maastricht and the Stability Pact endorsed in Amsterdam on June 16-17 1997. The methodological approach used to understand the new policy environment is to go back and analyses what appear to be three distinct regulatory policy periods that span the years 1962-1981, 1981-1992 and 1992 to the present date.